Ações afirmativas e universidade: uma discussão do sistema de cotas da UFMA - Maciel, Regimeire Oliveira (2009)
The various inequalities experienced by black people in Brazil are directly related to the role of racism in the process of distribution of opportunities, rights and powers. The affirmative action policies have their reasons on the need to cope with this reality. This thesis aims to analyze the relationship between affirmative action policies and public universities through a system of quotas for black students at the Federal University of Maranhão - UFMA. Specifically discuss the implementing process of this system by analyzing the strategies used to approve this program and the performance of the main subjects involved. In this work, we start with the assumption that affirmative action policies are potentially designed to fight the effects of racism in various dimensions of Brazilian society. Similarly, it can realize some aspects of the democratization of higher education in Brazil if we consider that the implementation of these policies will increase, significantly, the access of poor and black students at that level of education and it will encourage the recognition of Brazil as a country racially unequal. Moreover, the affirmative action initiatives will enable the introduction of a variety of knowledge within the university and encourage the production of academic knowledge from other benchmarks